Collaborative System for Friday Preacher Scheduling - Hariandi Maulid; Indra Azimi; Amir Hasanudin Fauzi; Parman Sukarno (IJAIT (International Journal of Applied Information Technology), 2019)
In 2016, we have started to develop a collaborative system for Friday prayer scheduling. The system was intended to cope with some problems that corresponded with the high probability collision occurrences while compiling a timetable. In order to measure the effectiveness of the system implementation, we undertook a survey that started from late 2017 to September 2019. We observed the implementation of the system throughout the years and investigated the impact of its implementation. The objective of this research is to determine whether the system can diminish the collision rates and foster a user-friendly experience both for MTM and client users in managing, requesting, compiling, viewing and organizing the schedules. The pre and post- questionnaires clearly indicated that the system managed to diminish or almost deal with all the problems that regularly occurred during timetable compilation. In regard to usability, users found that the system was useful and easy to use as the system gained the highest possible score for overall satisfaction.